Notes from the field: silence kills! : Women and the transitional justice process in post-revolutionary Tunisia - Gray, Doris H. (International journal of transitional justice, 2013)
This article is based on the first collection of testimonies of female former political prisoners in Tunisia. Relying on purposive rather than random sampling, the interviews were aimed at contributing to an authentic Tunisian process of transitional justice that takes cultural, religious and gender-based norms into consideration. To date, the voices of conservative Islamist women detained under the Tunisian dictatorship have been significantly absent from the national discourse on transitional justice. Select voices of women are presented here that can begin to address this gap. The newly elected provisional government, in which the Islamist Ennahda Party enjoys a majority, has established a Ministry of Human Rights and Transitional Justice, the first of its kind in the world. While this augurs well for Tunisia’s future, there is fear that the transitional justice process may nonetheless be captured by political agendas.